1998
DOI: 10.1111/j.1523-1739.1998.96480.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Forest Management and Conservation of Biodiversity in Tropical Forests

Abstract: As a reaction to the continued dwindling of tropical forest resources, many research and development organizations have turned to the idea of natural forest management in the hope of making tropical forest lands more profitable while maintaining biodiversity. Assertions of sustainability in logging practices have been inadequately supported, however. We begin with a review of the present knowledge of the effects of logging operations on various organisms. Post-harvest surveys of a spectrum of tropical forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 51 publications
1
41
0
2
Order By: Relevance
“…The worry is that previous surveys (including ours) have demonstrated that these patchy oak forests still contain unusual levels of biodiversity and many uniquely Mexican taxa of plants and animals (Peterson et al 1993), thus fragmentation and loss of forests can broadly be expected to lose substantial amounts of biodiversity over the long term (e.g. Bawa and Seidler 1998).…”
Section: Discussionmentioning
confidence: 98%
“…The worry is that previous surveys (including ours) have demonstrated that these patchy oak forests still contain unusual levels of biodiversity and many uniquely Mexican taxa of plants and animals (Peterson et al 1993), thus fragmentation and loss of forests can broadly be expected to lose substantial amounts of biodiversity over the long term (e.g. Bawa and Seidler 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In general, forest modification and clearance have negative impacts on biodiversity (e.g. Bawa and Seidler 1998) and, each 1% reduction of natural area will cost about 1% of steady-state diversity (Rosenzweig 2003). Thus, preserving small tracts of wild habitat can only delay these reductions (Rosenzweig 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Various anthropogenic causes have been attributed to this decline (Brown and Paxton 2009). However, the destruction of tropical forest worldwide (Bawa and Seidler 1998) is certainly among the most important (Freitas et al 2009). In this scenario, the main genetic threat to bees comes from the loss of genetic diversity associated with declines in population sizes, a picture that can be severely aggravated when gene flow is limited or disrupted, leading to the potential extinction of local populations (Frankham et al 2010).…”
Section: Introductionmentioning
confidence: 99%